Evaluación de gravedad en pacientes agudos - Medel F, Juan Nicolás; Ugalde C, Diego (Revista Hospital Clínico Universidad de Chile, 2022)
Severity meaning the risk of adverse outcomes, death or disability, varies along disease’s characteristics and patient related factors. Its evaluation is complex and besides subjective perception several, more objective, clinical tools exist along with laboratory data that independently or used in combination, allows the clinician to approach severity of a given patient’s condition or a particular disease. We will review several aspects of the evaluation of severity, clinical and laboratory based in addition of some scoring systems, emphasizing perfusion and organ dysfunction evaluation as key elements to assess severity particularly in critical situations.